Utilização de dutos descartados do gasoduto Coari-Manaus para confecção de ponte provisória sobre o Igarapé do Cedro segundo a norma API5LX70 - SANTOS, Doriel Andrade dos (Universidade Federal do Pará, 2012)
This paper aims to present an alternative construction of an engineering project, with the use of API 5L X70 pipeline discarded the Coari-Manaus, in the process of building a temporary bridge over the Cedro affluent of the Amazon rainforest, to enable transport workers and materials for industrial production of construction Compression Station - ECOMP in Juaruna. To verify the behavior of an element of the bridge, we used the ANSYS 8.0 program that applies the method to numerical analysis of stresses and deformations of structural elements subjected to stresses. It also presents a proposal for mitigation of environmental impacts caused by the equipment at the crossing of the affluent of Cedro and the logistical challenges faced by transportation companies in the Amazon region.